Total-Genome Analysis of BRCA1/2-Related Invasive Carcinomas of the Breast Identifies Tumor Stroma as Potential Landscaper for Neoplastic Initiation - Weber, Frank (The American Society of Human Genetics, 2006)
We have shown that the tumor microenvironment of sporadic breast cancer is diverse in genetic alterations and contributes to the cancer phenotype. The dynamic morphology of the mammary gland might be of special interest in hereditary breast/ovarian cancer syndrome (HBOC). We hypothesized that hotspots of loss of heterozygosity or allelic imbalance (LOH/AI) within the tumor stroma of BRCA1/2-related breast cancers provide an impaired mammary stroma that could facilitate later malignant transformation of the breast epithelium. We conducted a total genome LOH/AI scan of DNA derived from the epithelium and stroma of 51 BRCA1/2-related breast cancers, using 372 microsatellite markers. We compared these data with those from a set of 134 sporadic breast cancers. HBOC-related breast cancers accumulated significantly more genetic alterations than did sporadic breast cancers. BRCA1/2-related breast cancer stroma showed LOH/AI at 59.7% of all loci analyzed, similar to the average frequency of LOH/AI observed in the epithelium (66.2%). This is remarkably different from sporadic breast cancers, for which the average epithelial LOH/AI frequency (36.7%) far exceeds the average stromal LOH/AI frequency (28.4%) (P=.03). We identified 11 hotspot loci of LOH/AI in the BRCA1/2 stroma, encompassing genes such as POLD1, which functions in DNA replication, and SDHB. In a subset of samples, enriched for BRCA1 cases, we found 45.0% overall LOH/AI in the stroma, which was significantly higher than the 41.8% LOH/AI observed in corresponding epithelium (P=.04). Together, our data indicate that, in HBOC-related breast cancers, the accumulation of genomic instability in the cancer stroma coincides with that in the neoplastic epithelium, and we postulate that such a genetically unstable stroma might facilitate a microenvironment that functions as a landscaper that promotes genomic instability in the epithelium and, subsequently, neoplastic transformation.